Steroid Induced Glaucoma: Dilemma Decoded - Shweta Tripathi; Shalini Mohan; Jatinder Singh Bhalla; Kanika Jain; Ashwini Kulkarni (Delhi Journal of Ophthalmology)
Topical and systemic steroids are used to treat many clinical conditions but its use is not without side effects. Amongst the ocular side effects cataract and glaucoma are prominent. With the rising magnitude of glaucoma, it has become imperative to understand the pathophysiology, risk factors and management of Steroid Induced Glaucoma. This review attempts to decode the dilemma.